Monkeypox Vaccination Strategy and Missed Opportunities in STI and HIV Prevention: An Urban Sexual Health Clinic's Experience During a Public Health Emergency. (7th January 2023) - Stewart, Jessica; Bartkus, Mary; Sperring, Heather; Ruiz-Mercado, Glorimar; Johnson, Samantha; Pierre, Cassandra
Abstract: Among individuals presenting for monkeypox vaccination, transition from an opt-out protocol for sexually transmitted infection (STI) and HIV risk assessment and testing to an opt-in protocol was associated with a substantial increase in missed opportunities for HIV pre-exposure prophylaxis and STI testing at an ambulatory sexual health clinic.